The Effect of Non-Performing Loans on Return on Assets at PT. Bank Bukopin Tbk Period 2012-2022 - Aprih Santoso (Fin Sinergy: Jurnal Manajemen Keuangan, 2023)
This research aims to determine the influence of Non Performing Loans on the Return on Assets at PT Bank Bukopin Tbk. The method used is explanatory research. The analytical technique employed statistical analysis with regression testing, correlation, determination, and hypothesis testing. The research findings indicate that the average value of the Non Performing Loans variable is 3.45%. The Return on Assets variable has an average value of 2.95%. Non Performing Loans have a negative and significant impact on the Return on Assets, with a regression equation of Y = 4.702 - 0.507X, a correlation coefficient of -0.619 indicating a moderate negative relationship, and a determination coefficient of 38.3%. The hypothesis testing reveals a significance of 0.032 < 0.05.